PF-26 The Use of Endemic Sulawesi Medaka Fish (Oryzias celebensis) as an animal model candidate - Dwi Kesuma Sari; Irma Andriani; Khusnul Yakin; Magfira Satya (Hemera Zoa, 2018)
Medaka fish (Oryzias sp) or also known as